EFFECT OF VIVA VIDEO MEDIA TO IMPROVE ENGLISH VOCABULARY MASTERY TO ENGLISH LEARNERS - Nadirah, Nadirah; Hermanses, Sam (Uniqbu Journal of Social Sciences, 2022)
The objectives of the research were to find out: (1) whether or the effect Of viva video media to Improve english vocabulary mastery in the Eighth-Grade of SMP Negcri 4 Baranti and (2) whether or the effect Of viva video media to Improve english vocabulary mastery in the Eighth-Grade of SMP Negeri 4 Baranti. This research employed mixed method design that applied experimental and control group. The population of the research was the Eighth Gradestudents of SMP Negeri 4 Baranti. Total number of population was 60 students and two classes of them were taken as sample by using cluster sampling technique, class VIII.B as experimental group and class VIII.C as control group. The number of each class was 20 students so the total sample of the research was 40 students. The result of data analysis showed that there was significant difference between achievement of the students the effect Of viva video media to Improve english vocabulary mastery Eighth Grade students of SMP Negeri 4 Baranti. It was proved by the mean score of experimental group was higher than control group in post-test (73.94> 63.94). Furthermore, the result of the t-test value (2.814) was greater than t-table (a = 0.05;df = 38; t-table = 2.0858) which means that H was accepted. The data analysis of questionnaire showed that the students had high interest toward the effect of viva video to improve vocabulary mastery. It was supported by 4 students (20%) who were strongly interested, 14 students (70%) who were interested and 2 students (10%) who were moderate. The mean score of students’ answers in questionnaire (79.55) was classified as interested category.Based on the data analysis, the researcher concluded that: (1) the effect Of viva video media to Improve english vocabulary mastery; (2) the effect Of viva video media to Improve english vocabulary mastery was interesting for the students.